Unleashing the mysterious link between COVID-19 and a famous childhood vasculitis: Kawasaki disease - Antoine Fakhry AbdelMassih; Aisha Said AbdelAzeam; Aya Ayad; Aya Yasser Kamel; Ayah Khalil; Basma Kotb; Dina Waheed; Esraa Menshawey; Fady Sefein; Farah Taha; Habiba-Allah Ismail; Ibrahim Osman; et al. (SpringerOpen, 2020)
Abstract Background Coronavirus disease 2019 (COVID-19) emerged as a small outbreak in Wuhan rapidly progressing into the deadliest pandemic since the Spanish flu of 1918. The disease was deemed trivial in children, until the reporting, few days ago, of an emerging pediatric multi-inflammatory syndrome mimicking Kawasaki disease (KD). Main body This report reveals that coronaviridae were implicated in induction of several post-infectious vasculitides, namely, KD, AHEI, and HSP. This occurs in genetically susceptible individuals to vascular inflammation. Shared genetic susceptibilities between KD and CoV include genes encoding for CD 40, HLAB-15:03, and ACE. This leads to augmented inflammation with hypersecretion of cytokines especially IL-6. Conclusion The revealed relationships between KD and CoV can help to predict the risk of KD in COVID-19 patients through screening levels of upregulated cytokines. It might also signify that classic treatment of KD with IVIG might need to be replaced with anti-cytokine therapy in COVID-19 patients.